An existence result for a new coupled system of differential inclusions involving with Hadamard fractional orders - Lili Zhang; Chengbo Zhai (Electronic Research Archive)
In this paper, we introduce a new coupled system of differential inclusions involving with Hadamard fractional orders. By applying a fixed point theorem for three operators containing $ x\in{AxBx+Cx} $ in Banach algebras, we get an existence result for the discussed system via multi-valued maps in a Banach space. An example is provided to support the validation of the theoretical result achieved.